Stink Bugs and Other True Bugs - Goldish, Meish; World Book, Inc. (Chicago : World Book, 2002)
Questions and answers provide information about a variety of bugs, including the stink bug, harlequin bug, and giant water bug.
Includes bibliographical references (p. 64) and index.
Keywords: Stinkbugs -- Juvenile literature; Hemiptera -- Juvenile literature